Premature Therapeutic Antimicrobial Treatments Can Compromise the Diagnosis of Late Periprosthetic Joint Infection - Shahi, Alisina (Clin Orthop Relat Res, 2015)
BACKGROUND: In the absence of positive cultures and draining sinuses, the diagnosis of periprosthetic joint infection (PJI) relies on laboratory values. It is unknown if administration of antibiotics within 2 weeks before diagnostic evaluations can affect these tests in patients with PJI. QUESTIONS/PURPOSES: The purpose of this study was to investigate the correlation of antibiotic administration with (1) fluctuations in the synovial fluid and serology laboratory values; and (2) sensitivity of the diagnostic tests in patients with late PJI (per Musculoskeletal Infection Society [MSIS] criteria). METHODS: Synovial white blood cell (WBC) count, polymorphonuclear neutrophil (PMN) percentage, and serum erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) as well as culture results were investigated in 161 patients undergoing total knee arthroplasty with late PJI diagnosed with the MSIS criteria. Depending on whether presampling antibiotics were used, patients were divided in two groups (53 [33%] patients were on antibiotics). The median laboratory values and the false-negative rates were compared between the two groups. RESULTS: The median of all variables were lower in the antibiotic group compared with the other group: ESR (mm/hr): 70 versus 85, difference of medians (DOM) = 15 mm/hr, p = 0.018; CRP (mg/L): 72 versus 130, DOM = 58 mg/L, p = 0.038; synovial WBC (cells/μL): 29,170 versus 46,900, DOM = 17,730, p = 0.022; and synovial PMN%: 88.5% versus 92.5%, DOM = 4%, p = 0.012. Furthermore, using the MSIS cutoffs, the false-negative rates of several parameters were higher in the antibiotic group; ESR: 19.2% (nine of 47) versus 6.1% (six of 99) (relative risk, 3.1; 95% confidence interval [CI], 1.2–8.3; p = 0.020); CRP: 14.9% (seven of 47) versus 2.00% (two of 100) (relative risk, 7.4; 95% CI, 1.6–34.4); PMN%: 23.1% (12 of 52) versus 9.4% (10 of 106) (relative risk, 2.4; 95% CI, 1.1–5.2; p = 0.027). Patients in the antibiotic group also had higher rates of negative cultures: 26.4% (14 of 53) versus 12.9% (14 of 108) (relative risk, 2.0; 95% CI, 1.05–3.9; p = 0.046). CONCLUSIONS: It appears that premature antibiotic treatments are associated with lower medians of diagnostic laboratory values. Thus, and in line with the guideline recommendations of the American Academy of Orthopaedic Surgeons, patients with suspected late-PJI should not receive antibiotics until the diagnosis is reached or refuted. LEVEL OF EVIDENCE: Level III, diagnostic study.